Peran Petugas TKSK dalam Membangkitkan Dukungan Sosial Terhadap Penerimaan Diri Eks. Pasien ODGJ Di Dinas Sosial P2KB Kota Pekalongan - ‘Aisy, Naila Rihhadatul; Muhammad Rifa’i Subhi (LPPM Politeknik Pratama, 2024)
Resocialization isa process of reintegrating back into society after a paranoid schizophrenic patient regardless of his status with a psychotic disorder. The existence of these studies served to understand and understand the dynamics of the exes. Odgj patients for social interactions after inpatient stay at pekalongan city mascot RPSBM, with the study using a qualitative method. The study involved the participants of the study of four individuals of the RPSBM under the supervision of the ministry, TKSK Pekalongan deputy northern allocation, former odgj patients, and families. The study a datausesbase of observation, interviews, and field notes. Several of these research processes have yielded results showing that it can produce exes. Patients to restore canonization as well as to reacquire exes. A patient in the community. At the ex. The paranoid schizophrenic patient can make a recovery through the treatment process that comes with family support, spiritual support, regardless of how important the treatment of the iconics is. Patient. The next attempt is the eks. Patients can optimize their social function as well as to avoid the stigma of letting go through a spiritual approach. With this in mind, the social support of any element of society can bring the exes. The patient is able to accept and understand himself as a conscious effort to be cured.